Single-centre telephone survey on patients' perspectives regarding remote paediatric outpatient consultations in a district general hospital. Issue 1 (7th December 2020) - Singh, Nilima; Datta, Manas
Abstract : During the COVID-19 pandemic, remote consultations became a new norm for paediatric outpatient clinics. The objective of this survey was to find patients' perspective on telephone consultations. 200 patients, who had remote consultations since April 2020, were surveyed and their responses were analysed. Almost half (98/200) of the patients or their parents preferred remote consultations mixed with face-to-face consultations; only a fifth (40/200) preferred exclusively face-to-face consultations; and approximately a third (62/200) preferred exclusively remote consultations. In conclusion, remote consultations are becoming a popular choice for patients, although there are limitations, especially in the context of safeguarding.